Parameters of training load in mountain runing as a factor of training process management - Bakaev V.V.; Poniasov O.E.; Vasilyeva V.S.; Punich S.V. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to increase the efficiency of pre-competition training of mountain running athletes through adaptation to extreme specific factors of competitive activity. Methods and structure of the study. The parameters of the training activity of eight qualified mountain running athletes aged 26.5±0.5 years were studied. The use of training loads was based on accentuated running uphill with a height gain of 1360 m in one workout. The principle of load specificity in mountain running has been implemented. Results and conclusions. The use of load indicators allows us to stimulate the deployment of additional reserves for increasing functional readiness in mountain running. The use of a two-peak variant of increasing the mountain running load in the content of a training session makes it possible to maintain the overall magnitude of the impact of the load on the athlete’s body while reducing the partial contribution of the total running intensity.